Sistema Web para consulta de frecuencias, determinación de rutas de viaje y reservación de boletos en las Cooperativas de Transporte de la terminal Terrestre "Reina del Cisne" de la ciudad de Loja. - Benítez Malacatus, Julio César (2014)
This draft Thesis (PFC) covers the analysis, design and implementation of a computer system for the query frequency, determining travel routes and ticket reservation (SIRPAL 1.0) cooperative transport of bus terminal "Reina of Cisne” in the city of Loja. The system streamlines the process of finding travel routes by constructing the algorithm to classify cooperatives with their frequencies, scales and costs, based on data of the place of departure and destination. In turn, the system allows air travel reservations using the Internet as a communication medium between the cooperative and the user. To develop the process of booking travel tickets we started from research to transportation cooperatives that have the highest number of frequencies to cantonal, provincial and international levels, and offered fleet service (normal transport - Special) through these factors determined the Loja International and Union Cariamanga International cooperative are entities that have greater demand, which is why these cooperatives to the respective sections ticketing management was built. The control of ticketing and reservations work based on the pictures of each cooperative work, where the distribution of frequencies between each unit (bus) is specified. In addition to meet the goals outlined in the PFC, data collection techniques was used as direct observation, survey, interview, scientific methods and deductive, inductive, descriptive, analytical, literature, science and development methodology Iconix software. The results and discussion indicate and demonstrate how the objectives were achieved, making a description of how they were building the modules in the system, its requirements, representation of the use cases, domain model and diagrams for able to obtain the proposed solution. Finally conclusions and recommendations obtained are presented.